Prevalence of endoparasites in village chicken (Gallus gallus domesticus) and wild jungle fowl (Gallus gallus spadiceus). - Reduan, Mazleen Laili; Babjee, Shaik Mohamed Amin; Kumar Sharma, Reuben Sunil (2010)
Thirty apparently healthy chickens comprising 15 adult wild jungle fowl (Gallus gallus spadiceus) and 15 free-ranged village chickens (Gallus gallus domesticus) were obtained from Jenderam Hulu in the district of Sepang, Selangor, Malaysia. From these samples, 3 of the village chickens were kept in a closed house system whereas the other village chickens were free ranged. All the wild red jungle fowls were caught from the Jinjarum in the district of Banting, Selangor. The nematodes species recovered from the necropsied 15 wild jungle fowls were Oxyspirura manson (32.6%) with mean intensity of 13.7 and Lemdana sp.(1.5%) with mean intensity of 3. Capillaria sp (0.5%) with mean intensity of 1.5. Tetrameres sp.(4.8%) with mean intensity of 6.5 and Heterakis gallinarum (10.85%) with mean intensity of 4.6. The cestodes recovered were Raillietina sp.(20.4%) with mean intensity of 11.1 and Hyemenolepis sp. (1.84%) with mean intensity of 1.03. Tanaisia sp.(26.5%) is the trematodes recovered with mean intensity of 26.5 and there is also the presence of Acanthocephala sp.(1.5%) with mean intensity of 2.25 in this group of chicken. In 15 village chicken, nematodes found were Oxyspirura mansoni (55.7%) mean intensity of 3.5, Lendana sp. (1.47%) with mean intensity of 31.3. Syngamus trachea (0.9%) with mean intensity of 2.5, Capillaria sp (0.7%) mean intensity of 1, Tetrameres sp. (4.8) mean intensity of 8.7, Ascaridia sp.(2.6%) mean intensity of 3.5 and Heterakis gallinarum (15.6%) with mean intensity of 8.5. The cestodes that were recovered were only Raillietina sp. (15.3%) with mean intensity of 8.7 and the trematodes were Tanaisia sp.(1.8%) with mean intensity of 10. From the results obtained, there was no significant difference in the endoparasites seen in village chicken and wild jungle fowl based on the T-test (P>0.05). The most common parasites in these two groups of chickens were the nematodes species Heterakis gallinarum.